Spreminjanje prepričanj učiteljev o samoevalvaciji šole ter vpliv na vedenje učiteljev in dosežke učencev - Hauptman, Alenka (Psihološka obzorja (Ljubljana), 2012)
The purpose of the present study was to examine if different ways of promoting school self-evaluation had an effect on changing teachers' beliefs about school self-evaluation, on their behaviour in the classroom and on student achievement. Although school self-evaluation in Slovenian primary schools is legally required; there are no uniform instructions about using it or even systematic research on its effectiveness. Our sample included 111 fourth grade teachers from 59 Slovenian primary schools and their 2153 students. The study was designed as an experimental study with three groups of schools and two separate measurements. Durability of changes in beliefs and behaviour of teachers was also included. Groups of schools differed on activities of school self-evaluation; the first group of schools was the control group, the other two were separated according to intensity of promoting school self-evaluation. The data were gathered from teachers and students. Teachers were asked about their beliefs of school self-evaluation and behaviour in the classroom. From students we gathered data about their achievement in mathematics and science at the beginning and end of school year and data about their teachers' behaviour in the classroom. Differences between the groups of schools were expected mainly at the teachers' beliefs about school selfevaluation and as well on teacher behaviour and student achievement. The results showed that teachers' beliefs are fairly stable, and a lot of time is needed to achieve changes. In our research we failed to prove the impact of promoting school selfevaluation on changing teachers' beliefs, which is very likely the result of research limitations. Change in beliefs is the basis for changing behaviour and achievement, but this happens over a longer timeframe.
Keywords: šole; samoevalvacija; učitelji; učenci; prepričanja; učna uspešnost